2014
DOI: 10.1177/1532673x14534062
|View full text |Cite
|
Sign up to set email alerts
|

“‘Do This! Do That!’ and Nothing Will Happen”

Abstract: How effective is unilateral presidential power? Recent developments have shifted presidential scholarship in the direction of a more institutional approach, and one of the most important tenets of this work holds that the president has the ability to make policy on his own. However, there is significant anecdotal evidence suggesting that agency responsiveness to executive orders is not at all guaranteed. This study leverages a unique data set tracing the implementation of executive orders across 10 government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Furthermore, there may be additional costs to revoking orders, given the possibility of intensifying political opposition (Warber ). Additionally, issuing executive orders often involves a lengthy bargaining process within the executive branch (Kennedy ; Rudalevige ). With these assumptions, I turn to developing a theory of executive order duration based on both executive order characteristics and the changing political environment.…”
Section: Theorymentioning
confidence: 99%
“…Furthermore, there may be additional costs to revoking orders, given the possibility of intensifying political opposition (Warber ). Additionally, issuing executive orders often involves a lengthy bargaining process within the executive branch (Kennedy ; Rudalevige ). With these assumptions, I turn to developing a theory of executive order duration based on both executive order characteristics and the changing political environment.…”
Section: Theorymentioning
confidence: 99%
“…For example, a question that has received surprisingly little attention in the literature on presidential unilateral action is the implementation of such actions by bureaucratic agents. One exception is Kennedy (2015), who found that orders are not always fully implemented. One drawback of Kennedy's approach is that he focused on rulemaking as an indication of whether the order was implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Of looming significance is whether governors engaging in unilateral actions ‐ the issuance of an executive order ‐ can reach their desired policy outcome. While much of the related scholarship is focused on the presidential level, it is increasingly clear that executive orders are not self‐executing even among government agencies (Kennedy, 2015) and that public support is an important precondition of use (Christenson & Kriner, 2019). Coupled with the findings detailed here, executive authorities appear to be increasingly constrained in their ability to act unilaterally and achieve policy success; such a finding is particularly acute when policy directives, like mask mandates, require large‐scale acceptance.…”
Section: Discussionmentioning
confidence: 99%